Efek Pemberian Statin terhadap Proliferasi Endothelial Progenitor Cell pada Darah Tepi Penderita Penyakit Jantung Koroner Stabil - Feranti Meuthia; Yudi Her Oktaviono; Djoko Soemantri (The Indonesian Heart Association, 2017)
Background: Atherosclerotic lesions develop as the result of an inflammatory process initiated by endothelial damage. Endothelial progrenitor cells (EPCs), which is derived from bone marrow, participate in endothelial repair and new vessel growth. Cardiovascular pharmacotherapies have been shown to improve overall numbers and function of EPCs in patients with cardiovascular risk and cardiovascular disease. Studies have reported that statins exert beneficial effects on EPCs by enhancing EPC proliferation and differentiation. Thus, we require a research to analyze the effects of three different statins on EPC proliferation. The objective of this study is to analyze the effect of statins on EPC proliferation from peripheral blood of stable coronary artery disease patient.Methods: This is an in vitro true experimental post-test only control group design. The mononuclear cells (MNCs) were isolated from peripheral blood of stable coronary artery disease patient and were cultured in CFU-Hill medium for three days. Then samples were put into four groups, simvastatin experiment group, atorvastatin experiment group, rosuvastatin experiment group and control group. Each experiment group was divided into three subgroups with different doses, 0.1 ?mol/L, 0.5 ?mol/L, and 2.5 ?mol/L then incubated for 48 hours. EPC proliferation was evaluated afterwards with MTT cell proliferation assay. Immunocytochemistry method was performed for EPC identification to evaluate expression of CD34+. CFU-Hills were observed to confirm functional characteristics of EPC. Data were analyzed by independent T-test and ANOVA.Results: MTT cell proliferation assay showed a significant increase of EPC proliferation in simvastatin, atorvastatin, and rosuvastatin groups compared with control group (0.237±0.007, 0.248±0.01, 0.231±0.008 vs 0.17±0.008, p<0.05). It also revealed significant difference in EPC proliferation between each experiment groups, which atorvastatin showed the highest effect. EPC proliferation in atorvastatin is higher than simvastatin group (0.248±0.01 vs. 0.237±0.007, p<0.05), and simvastatin is also higher than rosuvastatin group (0.237±0.007 vs. 0.231±0.008, p<0.05). CFU-Hill counts demonstrated highest number in rosuvastatin group, followed by atorvastatin, and simvastatin. Immunocytochemistry showed positive expression of CD34.Conclusion: Statins increase EPC proliferation from peripheral blood of stable coronary artery disease patient. Atorvastatin showed the highest EPC proliferation, followed by simvastatin, and rosuvastatin. Each statins increased EPC proliferation dose-dependently.